PESANTREN DAN DAKWAH MULTIKULTURAL - Rosidi, Rosidi (BINA' AL-UMMAH, 2013)
The study of pesantren is still interesting for researchers as it isinseparable from Muslim life in Indonesia. Since its presence, thepesantren aims at educating prospective Muslim propagators whowould understand Islam well (tafaquh fi al-din) and local wisdomdifferent from one place to the others. Recent phenomenon shows thatthe Indonesian pesantren is vulnerable to the infiltration of newIslamic stream that conveys Islamic mission (rahmatan lil alamin)in more radical ways. Many acts of violence in this country arealways associated with this radical Islamic stream. However,radicalism is in fact contrary to the pesantren’s tradition that teachesIslam with humanistic and tolerant approaches. This article willaddress the following questions: how does dakwah in the pesantrenrespond to the acts of violence conducted by radical Muslims? Whatefforts have the pesantren done and how should dakwah in thepesantren be conducted to prevent religious radicalisation? Theresults of this study show that dakwah by means of radicalmovement does not constitute an “indigenous” product of thepesantren. Rather, it is imported by a certain pesantren from otherpart of the Muslim world. Multicultural dakwah approaches whichare performed legally, constitutionally and emphatically have beeninitiated by the pesantren and the government. Nevertheless,cooperation from multi-stakeholders within Islamic community isneeded to increase and intensify such efforts.Kata Kunci: Pesantren, Dakwah, Multikultural